Feasibility study for ballet e-learning: automatic composition system for ballet enchainement with online 3D motion data archive - Umino, B.; Longstaff, J. S.; Soga, A. (Research in Dance Education, 2009)
This paper reports on `Web3D dance composer` for ballet e-learning. Elementary petit allegro ballet steps were enumerated in collaboration with ballet teachers, digitally acquired through 3D motion capture systems, and categorised into families and sub-families. Digital data was manipulated into virtual reality modelling language (VRML) and fit to an animated dancer. Movements were segmented and stored in the motion data archive to be freely combinable in sequences by an algorithm for automatic generation of enchaînement conforming to principles of balletic aesthetics. An online interface was created containing controls for automatic composition and the 3D display. In an assessment of the system by expert ballet teachers only 8% of automatically generated enchaînements were inappropriate for ballet lessons, with 65% appropriate for elementary level and 75% rated as danceable by elementary level students. Interviews revealed that the system provided a creative resource for new enchaînements usable in ballet education by teachers and students.